Home monitoring of implantable cardioverter-defibrillators: interpretation reliability of the second-generation "IEGM Online" system - Nägele, Herbert; Lipoldová, Jolana; Oswald, Hanno; Klein, Gunnar; Elvan, Arif; Vester, Ernst; Bauer, Wolfgang; Bondke, Hansjürgen; Reif, Sebastian; Daub, Claudia; Menzel, Frank; Schrader, Jürgen; et al. (Europace, 2015)
AIMS: Intracardiac electrograms (IEGMs) are essential for the assessment of implantable cardioverter-defibrillator (ICD) function. The Biotronik Home Monitoring systems transmit an 'IEGM Online' that is shorter than the full-length programmer IEGM due to technical constrains. The aim of this study was to evaluate the accuracy of the physician's classification of the underlying rhythm based on the second-generation IEGM Online. METHODS AND RESULTS: In total, 1533 patients treated with single- and dual-chamber ICDs and cardiac resynchronization therapy defibrillators were enrolled at 67 investigational sites and followed for 15 months. The investigators classified the rhythm shown in IEGM Online as ventricular tachycardia, ventricular fibrillation, atrial fibrillation, other supraventricular tachyarrhythmia, oversensing due to lead failure, T-wave oversensing, or other rhythm. At the next in-office follow-up, the investigators classified independently the rhythm seen in the corresponding programmer IEGM. The two rhythm classifications were compared thereafter. Both IEGM Online and programmer IEGM were available in 2099 arrhythmic or oversensing events, of which 146 (7.0%) were classified as other rhythm or artefacts and were excluded as inconclusive or atypical. The remaining 1953 events, affecting 352 patients (23.0%), were classified correctly in 1803 cases (92.3%). The accuracy of rough rhythm classification as ventricular, supraventricular, or oversensing was 97.2%. CONCLUSION: The Lumax and IEGM Online HD Evaluation study demonstrates that remote IEGM analysis is reasonably accurate in a remote monitoring system that transmits shorter IEGM than the full-length programmer IEGM for the sake of frequent, fully automatic data transmission.
Keywords: Observer Variation; Sensitivity and Specificity; Home monitoring; Implantable cardioverter-defibrillator; uživatelské rozhraní počítače; Reproducibility of Results; Electrocardiography; Female; Male; Online Systems; Telemedicine; Humans; lidé středního věku; Treatment Outcome; User-Computer Interface; mužské pohlaví; Remote monitoring; Defibrillators, Implantable; elektrokardiografie; senzitivita a specificita; lidé; Intracardiac electrogram; ženské pohlaví; Arrhythmias, Cardiac; defibrilátory implantabilní; odchylka pozorovatele; on-line systémy; reprodukovatelnost výsledků; telemedicína; srdeční arytmie; výsledek terapie; Arrhythmia detection; Middle Aged